Evaluating Tumour Marker Utilization in a Rural Tertiary Care Teaching Hospital: Insights from a Clinical Laboratory Audit in the Konkan Region - Jankar, Jayshri Sadashiv; Yadav, Arvind S.; Golambade, Karan (Asian Pacific Journal of Cancer Care, 2026)
Introduction: Tumour markers are biochemical entities used to aid in diagnosis, prognostication, and therapeutic monitoring of malignancies. However, their utility in rural healthcare settings remains underexplored. This study aimed to audit the utilization patterns of tumour marker assays in a rural tertiary care hospital, evaluate their appropriateness in clinical context, identify potential misuse, and propose actionable recommendations for rational test ordering. Materials and Methods: A retrospective audit was conducted on 477 patients over two years (June 2021–June 2023) in the Central Clinical Laboratory of BKL Walawalkar Hospital. Data were analyzed by sex, departmental origin (IPD/OPD), type of tumour marker ordered, and clinical relevance as per established guidelines. Tumour markers included PSA, CEA, CA-125, CA 19-9, AFP, and B-HCG. Results: Females constituted 54.1% of the cohort. PSA (21.3%) and CEA (21%) were the most commonly ordered tests. CA-125 and B-HCG were largely requisitioned by OB-GYN departments. A mismatch was observed between test ordering patterns and guideline-based indications in several instances, particularly for PSA and CEA, with evidence of redundant or non-indicated requisitions from departments with low oncology involvement. Conclusions: While tumour markers are indispensable tools in oncology, this audit reveals significant gaps in their utilization, especially in departments lacking direct oncologic focus. The findings underscore the need for institutional guidelines, education on appropriate test use, and periodic audits to promote diagnostic stewardship in resource-limited rural settings.